Polyarteritis nodosa presenting with catastrophic involvement of the intra-abdominal arterial tree - Gwenno Edwards; Abdulfattah Alejmi; Janice Harper (Archives of Renal Diseases and Management - Peertechz Publications, 2021)
We report a case of a 63-year-old female presenting with abdominal pain, who suffered a dramatic deterioration in her condition following a diagnosis of bilateral renal infarcts on imaging. Within days she had developed widespread aneurysmal dilatation, dissection and thrombosis of the intra-abdominal arterial tree, requiring emergency transfer to a tertiary vascular centre for treatment of polyarteritis nodosa. She responded well to intravenous cyclophosphamide and is now receiving treatment on an outpatient basis.